MEMAKNAI TRADISI TAU TAIS DAN PENGARUHNYA TERHADAP PENGEMBANGAN IMAN KAUM PEREMPUAN SUKU TAHILA PERSPEKTIF MULIERIS DIGNITATEM - Asti Molo, Agustina; Benitius Metom, Philipus; Habu Lelo, Elmagondulfa (JURNAL PROPHETA, 2024)
The Tahila tribe is a community group that always tries to preserve culture. The culture that is always passed down is tau tais. Tau tais is a tradition that has been carried out by the people of the Tahila tribe since time immemorial. In this tradition they are directed to change bad habits that always cause problems. The problem that often occurs in the Tahila tribe is regarding the position of women (wives) in front of their husbands. This situation makes some women feel depressed and down so that in the end they close themselves off from being involved in social activities and religious activities.This research aims to determine: (1) the influence of the tau tais tradition on the development of the faith of Tahila tribe women; and (2) the meaning of the tau tais tradition in the Mulieris Dignitatem perspective. The model or type of research used by the author is a descriptive method. The research was carried out using a qualitative approach or research based on nature (natural settings) with the data sources being traditional leaders, community leaders, religious leaders and women figures in the Tahila Tribe. The Tahila Tribe is a community group that is involved in all activities, be it social, economic or religious activities. Their involvement really ensures the continuity and existence of culture. However, the issue of the role and position of women is a problem that exists in the Tahila tribe. Women are considered a secondary group and are only recognized as a complementary and additional group. Therefore, the tau tais tradition has become a real manifestation and step to change the bad views of society, especially their husbands, towards women.